2020
DOI: 10.1002/ijc.33428
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the endometrial microbiota and its association with inflammatory cytokines in endometrial cancer

Abstract: The underlying molecular mechanisms involved in the pathogenesis of endometrial cancer (EC) are still not well understood. Our goal was to investigate the composition of the endometrial microbiota and the association with inflammatory cytokines in EC. Endometrial microbiota profiles of women with EC (n = 25) and benign uterine lesions (BUL, n = 25) were assessed by 16S ribosomal RNA gene amplicon sequencing. The expression levels of interleukin‐6 (IL‐6), interleukin‐8 (IL‐8), and interleukin‐17 (IL‐17) mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 49 publications
6
83
3
Order By: Relevance
“…Where there is persistent dysbiosis of the microbial environment, altered immune and metabolic signaling can result in oxidative stress and the recruitment of immune cells which release reactive oxygen species (ROS), which may result in inflammation–driven carcinogenesis ( 40 , 41 ). At present, the study of endometrial microbiota has reported that EC is associated with particular microorganisms ( 42 ). Similarly, related studies have also indicated that many microorganisms are involved in the development of EOC, such as Proteobacteria and Firmicutes ( 43 ).…”
Section: Hypothesis Of Eovc Originmentioning
confidence: 99%
“…Where there is persistent dysbiosis of the microbial environment, altered immune and metabolic signaling can result in oxidative stress and the recruitment of immune cells which release reactive oxygen species (ROS), which may result in inflammation–driven carcinogenesis ( 40 , 41 ). At present, the study of endometrial microbiota has reported that EC is associated with particular microorganisms ( 42 ). Similarly, related studies have also indicated that many microorganisms are involved in the development of EOC, such as Proteobacteria and Firmicutes ( 43 ).…”
Section: Hypothesis Of Eovc Originmentioning
confidence: 99%
“…Winters et al also sequenced endometrial samples from 25 women who underwent total hysterectomy for fibroids or endometrial hyperplasia, and found that the most abundant genera in their endometria were Acinetobacter , Pseudomonas , Comamonadaceae , and Cloacibacterium [ 30 ]. Finally, in a more recent study, Lu et al also suggested that Lactobacillus is not the predominant genus in the endometrium, observing a greater abundance of Rhodococcus , Phyllobacterium , Sphingomonas , Bacteroides , and Bifidobacterium [ 31 ] ( Table 1 ).…”
Section: Endometrial Microbiomementioning
confidence: 99%
“…This decrease in the diversity of microorganisms led to the overgrowth of the few remaining species and a decrease in resilience. Furthermore, in this study, Pseudomoramibacter_Eubacterium , Rhodobacter , Vogesella , Bilophila , Rheinheimera , and Megamonas were enriched in patients with benign uterine lesions, while Micrococcus was associated with an inflammatory profile in endometrial cancer [ 31 ].…”
Section: Microbiome and Endometrial Cancermentioning
confidence: 99%
“…Similarly, the metabolization of alcohol by oral microbiota to produce acetaldehyde interferes with DNA repair and enhances chromosomal damage. In addition to the role of gut and breast microbiome in cancer pathogenesis, disturbances in bladder, ovarian, vaginal, uterine, male genital tract, and pulmonary microbiome can also initiate local carcinogenicity(El-Sayed et al 2021a ; Haque et al 2021 ; Lu et al 2020 ; Perrone et al 2021 ; Thomas et al 2021 ; Tuominen et al 2021 ), and in addition to the role of some microbiota in cancer development, many members of our virome are also incriminated in triggering various types of cancers(Haque et al 2021 ). It is of high interest that the microbiota not only induce cancer but they can also interact with cancer therapeutic protocols.…”
Section: Microbiome-induced Diseasesmentioning
confidence: 99%